Towards a structural constitution: contribution of Presidential Succession Law to the Constitution of Indonesia - Febriansyah Ramadhan; I Gede Agus Kurniawan; I Gede Druvananda Abhiseka; Putu Wahyu Widiartana; Roqiyul Maarif Syam (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study examines the relatively underexplored domain of presidential succession within constitutional law, which addresses the critical scenario in which the offices of the President and Vice President simultaneously become vacant. Despite its importance, the conceptual frameworks and defining characteristics of succession regimes have not been systematically or comprehensively mapped. To fill this gap, the present article establishes a strong theoretical foundation for presidential succession by applying doctrinal methods grounded in constitutional analysis, comparative law, and conceptual inquiry. Furthermore, it synthesises and organises the salient features of succession provisions as they appear across a variety of national constitutions. Employing a comparative constitutional approach, the research aggregates these dispersed elements to illuminate common patterns and divergences. The findings suggest that a more advanced articulation of succession rules could substantially enhance the structural integrity of Indonesia’s 1945 Constitution, elevating it toward a fully automated and systematised mechanism that minimises discretionary discretion, resists political interference, and guarantees continuity of executive authority. Finally, the catalogued key features offer a fertile basis for further empirical and normative investigation aimed at identifying the optimal configuration of succession clauses for any given constitutional order.